PELAYANAN PENDIDIKAN INKLUSIF BAGI TUNANETRA (STUDI KASUS DI IAIN IMAM BONJOL PADANG) - Meri Susanti; Nora Zulvianti (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2018)
Blindness is a term for individuals who experience interference in terms of vision and need aids in daily activities, and also to support the educational process. Educational services for blind people in educational institutions are generally referred to as inclusive education. This inclusive education model emphasizes full integration, eliminates the labeling of children with the principle of "Education for All". Inclusive education services are held at regular education institutions. They are enforced and have the same rights and obligations. The implementation of education in regular educational institutions also has a negative side, because these educational institutions are not fully prepared to organize inclusive education, such as approaches and methods used by educators who are not in accordance with the characteristics of disability and their educational needs, and lack of facilities and infrastructure that can support the process education, especially if all related elements do not cooperate with each other, but this can hamper the development of their potential.